2001
DOI: 10.1046/j.0960-7692.2001.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two‐ and three‐dimensional ultrasound measurements of nuchal translucency

Abstract: The number of fetuses in which nuchal translucency could be measured tended to be higher with three-dimensional ultrasound, although the difference was not statistically significant. The possibility of rotating a stored volume and inspecting it in three orthogonal planes makes three-dimensional ultrasound a useful tool for nuchal translucency measurements, especially in doubtful cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…NT had been used as a standard marker in first trimester screening for Down syndrome, in combination with serum markers. Although Paul et al (2001) reported that NT measurement can be repeated only 60% in a 3D random volume, a number of studies regarding evaluation of NT using 2D and 3D sonography showed a good correlation between these two techniques at any position (Kurjak et al, 1999;Chung et al, 2000;Clementschitsch et al, 2001;Eppel et al, 2001;Michailidis et al, 2002;Worda et al, 2003;Shipp et al, 2006). We also agree with the results published by Shipp et al (2006) that 3D sonography would be potentially useful in scanning fetuses that are not in an optimal position.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…NT had been used as a standard marker in first trimester screening for Down syndrome, in combination with serum markers. Although Paul et al (2001) reported that NT measurement can be repeated only 60% in a 3D random volume, a number of studies regarding evaluation of NT using 2D and 3D sonography showed a good correlation between these two techniques at any position (Kurjak et al, 1999;Chung et al, 2000;Clementschitsch et al, 2001;Eppel et al, 2001;Michailidis et al, 2002;Worda et al, 2003;Shipp et al, 2006). We also agree with the results published by Shipp et al (2006) that 3D sonography would be potentially useful in scanning fetuses that are not in an optimal position.…”
Section: Resultssupporting
confidence: 88%
“…Three-dimensional (3D) sonography has become more and more popular due to the low cost and high resolution. Some studies have shown a benefit in combining 3D with conventional two-dimensional (2D) scanning, with a decrease in acquisition time and improvement in image resolution (Kurjak et al, 1999;Chung et al, 2000;Clementschitsch et al, 2001;Eppel et al, 2001;Michailidis et al, 2002;Worda et al, 2003;Shipp et al, 2006). The Virtual Organ Computer-aided Analysis (VOCAL) volumetric calculation system has been installed in most modern 3D machines.…”
Section: Introductionmentioning
confidence: 99%
“…2). The occasional difficulty in obtaining a midsagittal view to measure nuchal translucency thickness at 11-14 weeks of gestation has led some [121][122][123][124] to In the upper-left image, the lines are placed at different levels. These planes demonstrate in one image from a single volume all the following structures and information: the four-chamber heart pointing to the left (HEART) and descending aorta on the left (AO), this situs solitus with the stomach filled in the left upper abdomen (ST), the aorta (AO) and inferior vena cava (IVC) in a normal position, the umbilical vein (UV), the gallbladder (GB) on the right side of the UV, the normal-appearing kidneys (KID), and the filled urinary bladder (BLAD).…”
Section: Multiplanar Mode Application In Routine Screening and Fetal mentioning
confidence: 99%
“…Increased NTT between 11 and 14 weeks of gestation is associated with an increased risk of chromosomal anomalies [173][174][175][176][177] and congenital heart defects. [178][179][180][181][182][183][184][185][186][187] The role of 3DUS in measuring the NTT has been addressed by several studies, 162,[188][189][190][191][192][193][194] with a subset comparing the performance of 2DUS and 3DUS for obtaining this measurement. 162,188,190,[192][193][194] When NTT measurements were attempted by the transvaginal route, most studies reported higher visualization rates for NTT by 3DUS, with no difference in mean NTT values between measurements obtained by 2DUS and 3DUS.…”
Section: Nuchal Translucency Thickness Measurementsmentioning
confidence: 99%
“…162,188,192 In contrast, visualization rates were similar when NTT was measured with transabdominal 2DUS or 3DUS. 190 In the study of Paul et al, 193 the authors took the original plane of acquisition into account when analyzing their results. For example, when 3D acquisition was performed with the fetus in a sagittal position, clear visualization of the NTT was achieved in most cases (38/40), in contrast to acquisitions performed with the fetus in random positions (24/40).…”
Section: Nuchal Translucency Thickness Measurementsmentioning
confidence: 99%